แนวทางพัฒนาการบริหารวิชาการของโรงเรียนประถมศึกษาเอกชนในกรุงเทพมหานครตามแนวคิดทักษะของคนในสังคม 5.0 - อจลา ศิริเสรีวรรณ (จุฬาลงกรณ์มหาวิทยาลัย, 2020)
This research aims to 1) study conceptual framework of academic management and people skills in society 5.0 2) study the current and desirable conditions of academic management development for private primary schools in Bangkok based on the concept of people skills in society 5.0 3) present the approaches for academic management development for private primary schools in Bangkok based on the concept of people skills in society 5.0. Mixed methods research are employed. The population was 362 private primary schools in Bangkok. The sample was 193 private primary schools in Bangkok. The data were collected from 579 school directors, and teachers. The instruments are conceptual framework evaluation form, questionnaire, and rating scale appropriability and possibility evaluation form. The data was analysed by frequency, percentage, mean, standard deviation, PNImodified, mode and content analysis. Research finding were 1) conceptual framework of academic management consisted of 4 elements which were curriculum development, learning management, development of material, innovation and learning resources and measurement and evaluation. Conceptual framework of people skills in society 5.0 consisted of 6 elements which were creative skills, digital skills, data analysis skills, interpretation and response to knowledge and information, critical thinking and scientific inquisition skills for solving complex problems, people management skills, and search and value creation skills. 2) the current conditions of academic management development for private primary schools in Bangkok based on the concept of people skills in society 5.0 was at high level. The desirable conditions was at the highest level. When considering each aspect found that current conditions of learning management for developing digital skill in society 5.0 was at the highest level (mean = 3.734) and curriculum development for developing data analysis skills, interpretation and response to knowledge and information in society 5.0 was at the lowest level (mean = 3.563). Desirable conditions learning management for developing creative skill in society 5.0 was at the highest level (mean = 4.550) and curriculum development for developing data analysis skills, interpretation and response to knowledge and information in society 5.0 was at the lowest level (mean = 4.451). 3) approaches for academic management development for private primary schools in Bangkok based on the concept of people skills in society 5.0 consisted of 4 approaches as follows: (1) develop material, innovation and learning resources in data analysis skills and people management skills in society 5.0 (2) develop measurement and evaluation in critical thinking skills and data analysis skills of people in society 5.0 (3) develop curriculum in critical thinking skills and creative skills of people in society 5.0 (4) develop learning management in critical thinking skills and data analysis skills of people in society 5.0